The Association Between Occupational Smoke Exposures and the Prevalence of Eye and Respiratory Health Conditions Among Commercial Fish Smokers in Abuesi, Ghana: A Cross-Sectional Self-Reported Study - Charity Owusu; Albert Ofori; Frank Adusei-Mensah; Carl Halladay Abraham; Samuel Kyei; Reginald Quansah; David Kofi Essumang (Environmental Health Insights)
Biomass smoke exposure represents a critical health concern, especially for those in occupational settings such as fish smoking. While substantial research has addressed indoor air pollution from domestic cooking, the specific risks faced by fish smokers have received insufficient attention. This study sheds light on the alarming relationship between smoke exposure and health issues among commercial fish smokers in Abuesi, Ghana. Through a comprehensive cross-sectional analysis involving 302 participants, we utilized structured questionnaires and expert eye assessments to gather vital data. Our statistical evaluation, including descriptive statistics, ANOVA, and chi-square tests, revealed a troubling prevalence of respiratory symptoms such as cough, asthma, and breathlessness, all significantly linked to prolonged smoke exposure. Eye health findings were equally concerning, with distant vision impairment affecting 26.37%, eye discomfort reported at 53.02%, and notable rates of cataracts (28.6%) and refractive errors (17.9%). For those suffering from breathlessness, asthma, and pneumonia, the data indicated that longer exposure durations correlated with more severe health outcomes. Specifically, subjects without breathlessness had an average smoking duration of 14.84 years (SD = 12.29) compared to just 10.26 years (SD = 11.15) for those with the symptom—a statistically significant P -value of .014. Asthma and pneumonia exhibited similar trends, highlighting a distressing reality: shorter smoking histories align with more severe health conditions, suggesting that such symptoms might drive smokers to abandon their practices prematurely. Given the serious health risks tied to traditional fish smoking practices, this study strongly advocates for the implementation of improved smoking technologies, better ventilation systems, and comprehensive health education initiatives. These measures are essential to safeguard the health of those involved in this vital industry and reduce exposure to hazardous smoke.